Assessing comprehension of spoken language in nonspeaking children with cerebral palsy: application of a newly developed computer-based instrument. - Geytenbeek JJM; Heim MMJ; Vermeulen RJ; Oostrom KJ (AAC: Augmentative & Alternative Communication, 2010)
This paper describes the development of an instrument to assess comprehension of spoken language in children with severe cerebral palsy (CP) who cannot speak, and for whom standard language assessment measures are not appropriate due to severe motor impairment. This instrument, the Computer-Based instrument for Low motor Language Testing (C-BiLLT), was administered to 42 children without disabilities (aged 14 months to 60 months) and to 18 children with severe CP (age 19 months to 71 months). Preliminary data showed that the instrument was acceptable to the children. Convergent validity was investigated by correlating C-BiLLT scores with test results on the well-established Reynell Developmental Language Scales (RDLS). Clinical implications and recommendations for future research are discussed.